Mortal doubt: transnational gangs and social order in Guatemala City - Fontes, Anthony (Atelier, 2018)
"The fact and fear of crime dominate Guatemala City. In the midst of unprecedented levels of postwar violence, Guatemalans struggle to comprehend the myriad forces that have made life in this city so deeply insecure. Born out of histories of state terror, migration, and deportation, maras (or transnational gangs) have become the veritable face of this new era of violence. They are brutal organizations engaged in extortion, contract killings, and the drug trade, and yet they have also become essential to the making of a certain kind of social order. Based on years of fieldwork inside prisons, police precincts, and gang-dominated neighborhoods, Anthony W. Fontes demonstrates how gang violence has become indissoluble from contemporary social imaginaries, and how these gangs provide cover for a host of other criminal actors. Ethnographically rich and unflinchingly critical, Mortal Doubt illuminates the maras' role in making and mooring collective terror in Guatemala City and beyond"--Provided by publisher